Association study between GSTT1 and GSTM1 polymorphisms and risk of preeclampsia in Chinese population. (September 2016) - Guan, Linbo; Fan, Ping; Liu, Xinghui; Liu, Rui; Chen, Yihong; Ye, Liyan; Chen, Jinxin; Zhu, Yue; Liu, Yu; Bai, Huai
Abstract: Context and objective: Preeclampsia is a pregnancy-specific disorder associated with oxidative stress. The glutathione S-transferases (GST) are a group of enzymes that protect cells from oxidative stress. Functional genetic polymorphisms of GST genes (GSTT1, GSTM1) have previously been reported. The aim of this study was to investigate the association of GST gene polymorphisms with the risk of preeclampsia in Chinese subjects. Study design: The case-control population consists of 525 subjects. The genotyping of the GSTT1 and GSTM1 polymorphisms was carried out on genomic DNA using the multiplex polymerase chain reaction (PCR). We calculated odds ratios (ORs), adjusted for the confounding variables, to estimate the association between gene polymorphisms and preeclampsia. Results: The GSTT1 null genotype was found to be protective from the development of preeclampsia (odds ratios 0.645, 95% confidence interval 0.421–0.989; P = 0.044). Further analysis showed that a combination of deletion genotypes of the GSTT1 and GSTM1 genes conferred an even lower risk of preeclampsia (OR = 0.470, 95%CI = 0.255-0.866; P = 0.015). There is no relationship between the GSTT1 and GSTM1 gene polymorphisms and blood pressure levels in pregnant women with and without preeclampsia. Conclusion: Our data suggest that a GSTT1 null polymorphism might be associated with decreased risk for preeclampsia in the Chinese population, and that this risk decreases with the combination of both GSTT1 and GSTM1 null polymorphisms.